TINJAUAN HUKUM ISLAM TERHADAP ADAT PALLANGKAI DALAM PRAKTIK PERNIKAHAN DI DESA GARUNTUNGAN KECAMATAN KINDANG KABUPATEN BULUKUMBA - Asriani Mardi; Muhammad Fajri (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
This research discusses the review of Islamic law on the Pallangkai custom. The main problem is how to review Islamic law on the Pallangkai custom in the practice of marriage in Garuntungan Village, Kindang District, Bulukumba Regency. This research is a qualitative research using a juridical and sociological approach to data sources because this research is a primary and secondary data source, then the data collection method used is interviews with documentation. The results of the study show that the traditional Pallangkai tradition is not disputed in Islam because it does not conflict with Islamic law. The Pallangkai custom is included in 'urf sahih, namely 'urf that is acceptable to the community. If the request for money or goods from the older brother can burden the man with a large demand and can prevent his sister from getting married. Included in 'urf Fasid is a habit that runs in society but its teachings are contrary to Islamic teachings because it has prevented someone from getting married. The suggestion of this research is that people's trust in interpreting the Pallangkai Indigenous tradition does not go out of the corridor of Islamic Law and still believes that happiness, safety and welfare in navigating married life only from Allah SWT not from Tradition. And for the brother, do not forbid the sister to marry first and burden the sister by asking for goods or anything excessively. Keywords: Custom, Marriage, Islamic Law Review